Application of Telemedicine in the Diagnosis of Oncogynaecological Diseases (Turkey Health Literacy Journal, 2025)
Abstract: Oncogynaecological diseases, including cervical, endometrial, ovarian cancers, and others, require a comprehensive and multi-layered approach to diagnosis and treatment. Early detection of these diseases is crucial for successful treatment and increasing survival chances. While traditional medical exams remain the foundation for diagnosis, telemedicine offers new ways of delivering these services, especially in situations where access to healthcare specialists is limited. The aim of this paper is to explore the applications of telemedicine in the diagnosis of oncogynaecological diseases, focusing on the advantages, challenges, and potential of this innovative technology. By analyzing current practices and research in this field, we will attempt to outline the future of telemedicine in oncogynaecology and its impact on women’s health.